Feedback regulation of Caulobacter crescentus holdfast synthesis by flagellum assembly via the holdfast inhibitor HfiA. Issue 2 (5th October 2018) - Berne, Cécile; Ellison, Courtney K.; Agarwal, Radhika; Severin, Geoffrey B.; Fiebig, Aretha; Morton, Robert I.; Waters, Christopher M.; Brun, Yves V.
Summary: To permanently attach to surfaces, Caulobacter crescentus produces a strong adhesive, the holdfast. The timing of holdfast synthesis is developmentally regulated by cell cycle cues. When C. crescentus is grown in a complex medium, holdfast synthesis can also be stimulated by surface sensing, in which swarmer cells rapidly synthesize holdfast in direct response to surface contact. In contrast to growth in complex medium, here we show that when cells are grown in a defined medium, surface contact does not trigger holdfast synthesis. Moreover, we show that in a defined medium, flagellum synthesis and regulation of holdfast production are linked. In these conditions, mutants lacking a flagellum attach to surfaces over time more efficiently than either wild‐type strains or strains harboring a paralyzed flagellum. Enhanced adhesion in mutants lacking flagellar components is due to premature holdfast synthesis during the cell cycle and is regulated by the holdfast synthesis inhibitor HfiA. hfiA transcription is reduced in flagellar mutants and this reduction is modulated by the diguanylate cyclase developmental regulator PleD. We also show that, in contrast to previous predictions, flagella are not necessarily required for C. crescentus surface sensing in the absence of flow, and that arrest of flagellar rotation does not stimulate holdfast synthesis. Rather, our data support a model in which flagellum assembly feeds back to control holdfast synthesis via HfiA expression in a c‐di‐GMP‐dependent manner under defined nutrient conditions. Abstract : Caulobacter crescentus produces a strong adhesive, the holdfast, to permanently attach to surfaces and form biofilms. In this study, we show that flagellum assembly is developmentally connected to the production of holdfast dependent upon both nutrient availability and c‐di‐GMP. These results provide new insight into the regulation of single cell adhesion and initial surface colonization leading to the process of biofilm formation.